Optimasi Pengendalian Suhu dan Kelembaban Kumbung Jamur Tiram Berbasis IoT Menggunakan Sensor AHT10 - Riskiono, Sampurna Dadi; Candra, Ade; Pranita, Elka; Nurrohman , Fatkhur; Tohir, Ahmat (JPM: Jurnal Pengabdian Masyarakat, 2026)
Kumbung Mas Tugi Mushroom Farm faces challenges in maintaining the stability of the oyster mushroom cultivation environment due to the manual water spraying method. This conventional practice causes fluctuations in temperature and humidity, thereby risking a decrease in harvest productivity. The objective of this study was to design and implement an Internet of Things (IoT)-based automatic condensation system to maintain microclimate stability inside the shed. The method applied was the design of a prototype using six AHT10 temperature and humidity sensors, each of which was controlled by an ESP32-C3 microcontroller and transmitted data wirelessly via the ESP-NOW protocol to a central server. The implementation results showed significant changes in the object where the system was able to work optimally and responsively. This system successfully maintained environmental stability consistently by automatically activating the pump when the average temperature exceeded 29°C and humidity was below 80%. Additionally, sensor accuracy testing demonstrated highly valid data, with an average temperature accuracy of 99.2% and humidity accuracy of 98.7%. In conclusion, this automation system successfully achieved the project's objectives by providing an effective solution for maintaining environmental stability and enabling convenient remote monitoring for farmers.